Dampak Pemutusan Hubungan Kerja terhadap Daya Beli Masyarakat dan Pertumbuhan Ekonomi Indonesia Tahun 2025 - Ahmad Wahyudi Zein; Ahmad Al Farabi; Fahreza Permana (Pajak dan Manajemen Keuangan, 2025)
This study aims to analyze the impact of layoffs (PHK) on the decline in people's purchasing power and Indonesia's economic growth in 2025. Layoffs are predicted to increase due to various factors such as tax hikes, subsidy restrictions, and decreased purchasing power. The study uses a quantitative method with secondary data from BPJS Ketenagakerjaan, Bank Indonesia, and other relevant institutions, as well as consumer survey data to measure the decline in purchasing power. The results show that layoffs significantly reduce people's purchasing power, which in turn negatively affects household consumption and national economic growth. The MSME and informal sectors are also affected by this decline in purchasing power. The study recommends policies that support industries prone to layoffs, revise layoff requirements, and maintain macroeconomic stability to prevent mass layoffs and minimize their impact on Indonesia's economy.